PEMAHAMAN PENGUNJUNG TERHADAP ARTI DAN FUNGSI ARBORETUM UNIVERSITAS RIAU - Napolion, Hongki; Sribudiani, Evi; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Arboretum is a collection or chard trees with a particular area contains various types of trees planted wherever possible to follow their natural habitat and are intended as a biodiversity conservation area and at least be able to improve or maintain the climatic conditions around the city of Pekanbaru. Arboretum of University  of Riau region has an area of ±10 ha. Arboretum is located in Pekanbaru City with a height of 5-50 m above sea level. The average temperature is 28-29 0C Arboretum with average humidity is 74-75%. This study aims to determine the visitor understanding of the meaning and function of Arboretum of University of Riau. This study will be conducted at the Arboretum of University of Riau. This research was conducted in December 2014 and January 2015. This is a descriptive study that attempted to describe exactly what data is being investigated. Based on the results of the research shows that the overall level of understanding of the visitors to the arboretum has been relatively high. Based on the classification of educational level of understanding of visitors to the arboretum is dominated by the high school level (high) due to the Arboretum located in the campus environment. While based on the classification level of understanding of visitors to the arboretum age 10-20 years of age (High), 21-30 years (Medium).   Keywords:Arboretum, understanding of visitors, University of Riau